Electrolyte Effects on the Faradaic Efficiency of CO 2 Reduction to CO on a Gold Electrode - Giulia Marcandalli (4560070); Akansha Goyal (8469546); Marc T. M. Koper (7288163) (2021)
The electrochemical reduction of CO 2 aims to be a central technology to store excess electricity generated by wind and solar energy. However, the reaction is hindered by the competition with the hydrogen evolution reaction. In this paper, we present a detailed quantitative study of the Faradaic efficiency (FE) to CO on a gold electrode under well-defined mass-transport conditions using rotating ring-disk electrode voltammetry. Varying the concentration of the bicarbonate and the electrolyte cation employing different rotation rates, we map out how these parameters affect the FE(CO). We identify two different potential regimes for the electrolyte effects, characterized by a different dependence on the cation and bicarbonate concentrations. For hydrogen evolution, we analyze the nature of the proton donor for an increasingly negative potential, showing how it changes from carbonic acid to bicarbonate and to water. Our study gives detailed insights into the role of electrolyte composition and mass transport, and helps defining optimized electrolyte conditions for a high FE(CO).